2017
DOI: 10.1039/c7cc01666b
|View full text |Cite
|
Sign up to set email alerts
|

Silver-mediated radical 5-exo-dig cyclization of 2-alkynylbenzonitriles: synthesis of phosphinylated 1-indenones

Abstract: A new silver-mediated 5-exo-dig cyclization of 2-alkynylbenzonitriles with disubstituted phosphine oxide and HO has been developed. The reaction enables multiple bond-forming events including C-P, C-C and C-O bonds under atmospheric conditions, leading to the concise and direct formation of 28 examples of phosphorus-containing 1-indenones with generally good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Here, either alkyne or alkynol is an alternate and versatile reagent for o‐halophenol to synthesis cyclic compounds due to its dual nature, both electrophilic and nucleophilic. A number of reports are published on the cyclization of alkyne via 5‐ exo ‐dig: for example silver‐mediated radical cyclization of 2‐alkynylbenzonitriles produced phosphinylated 1‐indenones and enediynes, a similar method also produced benzofulvenes . Likewise, Pd‐catalyzed 5‐ exo‐dig cyclization of alkyl amine with acid chloride offered excellent yield of switchable oxazolines and oxazoles.…”
Section: Introductionsupporting
confidence: 66%
“…Here, either alkyne or alkynol is an alternate and versatile reagent for o‐halophenol to synthesis cyclic compounds due to its dual nature, both electrophilic and nucleophilic. A number of reports are published on the cyclization of alkyne via 5‐ exo ‐dig: for example silver‐mediated radical cyclization of 2‐alkynylbenzonitriles produced phosphinylated 1‐indenones and enediynes, a similar method also produced benzofulvenes . Likewise, Pd‐catalyzed 5‐ exo‐dig cyclization of alkyl amine with acid chloride offered excellent yield of switchable oxazolines and oxazoles.…”
Section: Introductionsupporting
confidence: 66%
“…The use of bases, such as K 2 CO 3 and Et 3 N, was anticipatedt oi mprove this transformation, but very disappointed results were given (entries [3][4]. The use of other silver salts, such as silver acetate (AgNO 3 )a nd silver trifluoromethanesulfonate (AgOTf) completely suppressed the reaction process (entries13-14).T he following screening of oxidants revealed that di-tert-butyl peroxide (DTBP) and tert-butyl peroxybenzoate (TBPB) were found to have ad etrimental impact on the reaction yields (entries [15][16]. To our delight, the reactioni nt he presence of 2.0 equivalents of sodium methanesulfinate (CH 3 SO 2 Na) provided the expected 1-indenone product 3a,a lbeit with al ow 25 %y ield (entry 5), indicating that sulfinate salts could serve as ar adicalm ediatort oa chieve the radicalr elay process.…”
Section: Resultsmentioning
confidence: 99%
“…Without CF 3 CO 2 Ag or lowering its dosage, the unsatisfactoryo utcomes were observed (entries 10-12). The use of other silver salts, such as silver acetate (AgNO 3 )a nd silver trifluoromethanesulfonate (AgOTf) completely suppressed the reaction process (entries13-14).T he following screening of oxidants revealed that di-tert-butyl peroxide (DTBP) and tert-butyl peroxybenzoate (TBPB) were found to have ad etrimental impact on the reaction yields (entries [15][16]. The reaction gave ar elativelyl ower conversion when the reactiont emperature was adjusted to either 90 or 50 8C( entries 17-18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performing the reaction in MeCN at 80 8Cp roceeded readily with AgNO 3 as the oxidant, thereby allowinga ccess to 28 examples of phosphorus-containing 1-indenones 181 in 40-76 %y ields (Scheme 45 a). [73] This transformationi nvolved the addition of aP -centered radical, a 5-exodig cyclization, and hydrolysis (Scheme 45 b), thereby resulting in successive multiple bond-forming events, including the formationo fC ÀP, CÀC, and CÀOb onds in ao ne-pot manner. As a continuation of this work, the same group developed as ulfinate-salt-mediated radical relay strategy by using 2-alkynylbenzonitriles as radical acceptors, thereby affording aw ide range of 3-alkylated 1-indenones 183 in typically good yields.…”
Section: Radical-triggered Annulation/1n-bifunctionalization Reactionsmentioning
confidence: 99%